Deleuze and (Anti-)Dialectics - Kapelchuk, Ksenia (Stasis, 2019)
The article analyzes the critique of dialectics within the philosophy of Gilles Deleuze and the response to this critique that has been proposed by Slavoj Žižek. As a rule, Deleuze’s philosophy is considered to be anti-dialectical and anti-Hegelian. In lieu of this interpretation, Žižek has proposed an alternative reading whereby, Deleuze himself appears to be a dialectician and a Hegelian. The article attempts to answer the following question: in what sense can we consider Deleuze's philosophical project to be a dialectical one? The author reveals the different meanings of dialectics that are explicitly present in Deleuze’s works and also conducts an analysis of the implicit similarities—as identified by Žižek—between Deleuze's arguments and Hegel's philosophy. Thus, the author offers a comparative analysis of the concepts shared by Hegel and Deleuze (the virtual, chance, repetition), distinguishing between Deleuze's and Hegel's projects,as well as between their respective interpretations by Žižek.